Analysis of Resilience Priorities for Micro, Small and Medium Enterprises (MSMEs) in Deli Serdang District - Satria Tirtayasa; Januri; Hazmanan Khair; R.S. Kartaatmaja (Jurnal Manajemen & Agribisnis, 2021)
The COVID-19 virus pandemic during 2020 has become the material for research & investigation in building a priority model for the resilience of Micro, Small and Medium Enterprises (MSMEs). The purpose of this study is to provide empirical evidence on the resilience of MSMEs in coastal, urban and Plateau agricultural areas in Deli Serdang Regency, North Sumatra Province (PSU). Data collection techniques in this study are secondary data collection (the income and production aspects of one-quarter of MSME during the COVID-19 pandemic which is calculated by averages and regional positions), observation and interviews. The analysis technique used is the Analysis Hierarchy Process. The results show the trend of MSME resilience in the aspects of income and production, researchers who get production value always experience a general decline, so that prioritization in decision making in MSME resilience becomes a solution for decision-makers, product packaging, distribution networks and the need for agricultural and food products are priorities major for the community. Dissemination and guidance on awareness using a marketing model through social media for MSME actors has an impact on changing thinking and income, and the role of all decision-makers in obtaining information as an effective workflow and policy to build sustainable small and medium industries amid the COVID-19 pandemic. Keywords: agribusiness, analysis hierarchy process, north sumatera, resilience of small and medium enterprise